Conceptualizing participation in context for children and youth with disabilities: an activity setting perspective. (11th January 2013) - King, Gillian; Rigby, Patty; Batorowicz, Beata
Abstract: This article considers the conceptualization, operationalization and implications of "activity settings" for research on the recreation and leisure participation of children and youth with disabilities. Activity settings are contextualized settings that situate child and youth activities and their participation experiences. We discuss activity settings as an important construct for considering environmental qualities that provide opportunities for beneficial participation experiences for children and youth with disabilities. The article considers existing research using the concept of activity settings, the conceptualization of environment and contemporary issues in the measurement of participation and environment, indicating how these are addressed by an activity settings approach. We then describe the development of two quantitative measures of recreation and leisure activity settings – one assessing environmental qualities and the other assessing youth experiences – that have the potential to inform researchers, managers and clinicians about relationships between environmental qualities and participation experiences. Finally, we consider the implications of an activity settings approach for research, theory building and clinical practice. Implications for Rehabilitation: An activity setting perspective can enhance understanding of the recreation and leisure participation of children and youth with disabilities. The Measure of Environmental Qualities of Activity Settings (MEQAS) and Self-reported Experiences of Activity Settings (SEAS) provide unique assessments of environmental qualities and experiences from an activity setting perspective. Clinicians might use the SEAS alone to understand particular youth experiences in certain types of settings, which may be limiting or facilitating development. The combined use of the SEAS and MEQAS can provide experiential profiles linked to activity setting qualities such as structure, type of activity and social partners, providing a valuable source of information about youth programs.